ChMYB1-ChbHLH42-ChTTG1 module regulates abscisic acid-induced anthocyanin biosynthesis in Cerasus humilis - Xiaolong Ji; Zhe Li; Mingyu Zhang; Shaoyu Lang; Xingshun Song (Horticultural Plant Journal, 2024)
Cerasus humilis is a kind of economic fruit tree peculiar to China, which is widely used in the food, landscape, and pharmaceutical industries. Anthocyanins are a phenolic metabolite that plays an essential role in fruit coloration. However, the regulatory network of C. humilis in anthocyanin biosynthesis is still unclear. In this study, the R2R3-MYB transcription factor ChMYB1 was isolated from the full genome of the species. Yeast one-hybrid, dual-luciferase assays, and GUS staining showed that ChMYB1 significantly increased anthocyanin contents in C. humilis fruit by promoting the expression of ChCHS and ChUFGT by binding MBS (MYB-binding elements). ChMYB1 interacted with ChbHLH42 and ChTTG1 to form the MBW complex and further enhanced the expression of ChUFGT. In addition, abscisic acid (ABA) treatment promoted the expression of ChMYB1 and anthocyanin accumulation in C. humilis fruit. Interestingly, ABA treatment enhanced the interaction between ChMYB1 and ChbHLH42. Furthermore, ChABI5 inhibited the interaction between ChMYB1 and ChbHLH42. Our data elucidated the primary molecular mechanism of anthocyanin biosynthesis in C. humilis fruit, deepening the understanding of the regulatory network affecting anthocyanin metabolism in edible fruit crops.